O custeio por absorção como ferramenta de decisão para uma empresa no setor agroindustrial: o caso da indústria de polpa de coco - Rebelatto, Daisy N.; Aramayo, Jesús L. Salazar; Almeida, Mariana R. (Revista Gestão da Produção Operações e Sistemas, 2006)
This paper utilizes the financing method by absorption in order to analyze the structure of the productive costs of a specific organization, which sustains the case study undertaken here. Through this method, it was possible for the management staff to identify the main components of the organizational cost structure. Soon after, the dismemberment of such structure was performed, from which two analytic structures were extracted: costs (direct and indirect) and expenses. Such practice provided subsidies so that the management staff could identify, with a greater degree of trustability, which products of the compound promoted elevated contribution rates. Keywords: Financing methodologies; Pricing; Agribusiness.